Harmony annealing algorithm for curriculum-based course timetabling problem - Wahid, Juliana; Mohd Hussin, Naimah (2012)
This research article presents the adaption of the harmony annealing algorithm for solving timetabling problems, with particular focus on the curriculum-based course timetabling that formed part of the competition track 3 of the 2nd International Timetabling Competition in 2007 (ITC-2007). An attempt to solve these problems was made via an approach broken down into two parts; first, constructive algorithm with saturation degree approach was used to ensure a feasible solution, where the hard constraints are satisfied.Secondly, Harmony annealing algorithm was used to further improve the results obtained.The algorithm produced results that were not comparatively better than those previously known as best solution.With proper modification in terms of the approach in this algorithm would make the algorithm perform better on curriculum-based course timetabling.